Foreground Extraction of Surveillance Video Under Complex Background - Yu, Yue; Pan, Hong; Li, Xinde; Lin, Jiaxi (2018 IEEE 8th Annual International Conference on CYBER Technology in Automation, Control, and Intelligent Systems (CYBER), 2018)
In order to overcome the shortcoming of the origin ViBe algorithm, such as ghosting effects caused by moving objects in first frame, we present a novel foreground object extraction method based on an improved ViBe algorithm. In particular, we improve the initialization of ViBe to pick up more background information after the foreground object moving around the initialized samples. Then we use a median filter to reduce false detections. Experimental results show that our method can eliminate the ghosting effects effectively. For degraded surveillance video clips with camera jitter, we first apply the grayscale projection algorithm to stabilize the image and then use the proposed method to extract foreground object. Experimental results on some real-world surveillance video clips demonstrate the robustness of the proposed foreground extraction algorithm under different circumstances.